Gamma irradiation of chestnuts: dosimetric study and its influence in drying - Antonio, Amilcar L. (2012)
Food irradiation is a process that has been regaining an increasing interest for different food products to increase shelf life, for disinfestation or sterilization. In industry the drying of chestnuts is used to produce other sub-products, such as flour. So far as we know this is the first time that the influence of gamma irradiation in drying behaviour of an european chestnuts variety was performed. First the dose rate distribution was measured in one of the four levels of a Cobalt-60 irradiation experimental chamber to evaluate the uniformity dose during the irradiation process. The corners of a rectangle with the sample dimensions were chosen, being used the chemical Fricke standard dosimeter for dose rate estimation and routine Amber Perspex during irradiations. The average dose rate for the irradited positions was 2.1 ± 0.8 kGy h–1 , and the ratio Dmax/Dmin was 2.5. Afterwards the chestnuts were subjected to different doses (0, 1, 3 and 6 kGy), and then dried in a forced convective oven at 50 oC. The moisture ratios for each irradiation dose, as well as the drying rates, were determined. The Page model was used to modelize the drying behaviour, obtaining adjusted R squares higher than 0.98. Only the falling rate period was detected. At begininng the drying rates were high, decreasing very fast till 2 h of drying, after that the rates practically did not change till the end of the process. For the irradiation doses up to 6 kGy, it was observed a slight difference between non-irradiated and irradiated fruits drying behaviour.